(untitled) (Abril – NEPA / UFF, 2017)
Livro resenhado: VALDEMAR, António. Almada. Os Painéis, A Geometria e Tudo: as entrevistas com António Valdemar. 1ª ed. Porto: Assírio & Alvim, 2015. — DOI: http://dx.doi.org/10.22409/abriluff.2017n18a420